Potential role of sympathetic activity on the pathogenesis of massive pulmonary embolism with circulatory shock in rabbits - Wang, Yuting (Respir Res, 2019)
BACKGROUND: We recently showed that intravenous sodium nitroprusside treatment (SNP) could relieve the pulmonary vasospasm of pulmonary embolism (PE) and non-pulmonary embolism (non-PE) regions in a rabbit massive pulmonary embolism (MPE) model associated with shock. The present study explored the potential role of cardiopulmonary sympathetic activity on the pathogenesis and the impact of vasodilators on cardiopulmonary sympathetic activity in this model. METHODS: Rabbits were randomly divided into sham operation group (S group, n = 8), model group (M, equal volume of saline intravenously, n = 11), SNP group (3.5 μg/kg/min intravenously, n = 10) and diltiazem group (DLZ, 6.0 μg/kg/min intravenously, n = 10). RESULTS: MPE resulted in reduced mean arterial pressure and increased mean pulmonary arterial pressure as well as reduced PaO(2) in the M, SNP and DLZ groups. Tyrosine hydroxylase (TH), neuropeptide Y (NPY) and endothelin-1 (ET-1) expression levels were significantly increased, while nitric oxide (NO) levels were reduced in both PE and non-PE regions in the M group. Both SNP and DLZ decreased mean pulmonary arterial pressure, reversed shock status, downregulated the expression of TH, NPY and ET-1, and increased NO levels in PE and non-PE regions. CONCLUSION: Present results indicate that upregulation of the sympathetic medium transmitters TH and NPY in whole lung tissues serves one of the pathological features of MPE. The vasodilators SNP and DLZ could relieve pulmonary vasospasm in both embolization and non-embolization regions and reverse circulatory shock, thereby indirectly downregulating the sympathetic activation of the whole lung tissues and breaking a vicious cycle related to sympathetic activation in this model.